1974
DOI: 10.1002/bit.260160606
|View full text |Cite
|
Sign up to set email alerts
|

Mixing in anaerobic digestion

Abstract: SummaryThe mixing of the anaerobic digester contents significantly influences the efficiency of this operation; in particular, hydraulic dead zones are extremely detrimental to the reaction kinetics involved in anaerobic digestion. An analysis of the relative importance of thermal fluid movement in the digester to those caused by fluid inflow and outflow is presented. As an example, these principles are applied to a digester a t the South Bend Wastewater Treatment Plant. Experimental measurements, which have g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Early researchers have proposed various heating and mixing regimes to lower diffusion resistance. Some (Verhoff et al, 1974) have concluded that intermittent mixing is kinetically superior to complete mixing in anaerobic digesters. Mixing (sparging or draft tubes) with biogas appears to be superior to mechanical mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Early researchers have proposed various heating and mixing regimes to lower diffusion resistance. Some (Verhoff et al, 1974) have concluded that intermittent mixing is kinetically superior to complete mixing in anaerobic digesters. Mixing (sparging or draft tubes) with biogas appears to be superior to mechanical mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is widely believed that good mixing in such digesters is the key to efficient digestion and a number of studies have been made on the relationship between power input, mixing efficiency and digester performance (5). Ry contrast, the plug-flow digester requires no power for mixing, since it consists of an elongated horizontal reactor in which no intentional longitudinal mixing takes place.…”
Section: Resultsmentioning
confidence: 99%
“…Los primeros trabajos sobre la mezcla realizaban únicamente experimentos con trazadores y otros métodos de medición. Verhoff et al (1974) utilizaron fluoruro como trazador para medir el volumen de mezcla en digestores agitados con lanzas de gas, a nivel de laboratorio y en instalaciones industriales. Explicaron el fenómeno de mezcla en términos de principios físicos a través de un análisis teórico, destacando la importancia del empuje hidrostático, la convección natural y otras fuerzas de los fluidos.…”
Section: Antecedentesunclassified